Induksi Mutasi Tanaman Cabai Merah (Capsicum Annuum L.) dengan Ethyl Methanesulfonate pada Berbagai Tingkat Waktu Perendaman - WIARTANA, I MADE AGUS; PHARMAWATI, MADE; SUADA, I KETUT (Agrotrop : Journal on Agriculture Science, 2014)
Induction of Mutation of Red Chili (Capsicum Annuum L.) Using Ethyl Methanesulfonate at Several Soaking Periods. One way to increase genetic variation is through induced mutation usingchemical mutagen. Ethyl methanesulfonate (EMS) is a chemical compound that can cause mutationsand commonly used in plant. In this study seeds of red chili were treated using EMS 1% through seedsoaking. Seeds of red chili were soaked with EMS 1% in phosphate buffer pH 7 for 6, 9, 12 and 15hours at room temperature. As control, seeds were soaked in phosphate buffer pH 7. This study aimsto evaluate, physiological and reproductive characters of plants after treated with EMS. Experimentwas conducted in an open field with 5 replicates for each treatment. Results showed that concentrationof chlorophyll a, b and total chlorophyll increased in plants derived from seed treated with EMS 1% for9 hours compared to control and other soaking periods. Soaking seeds with EMS 1% for 12 hoursincreased viability of pollen compared to control and other treatments. The first time of floweringoccurred earlier at 6 and 9 hours soaking period.
Keywords: Ethyl Methanesulfonate; morphology; physiology; red chili; reproductive; soaking period